The Technology of Mud-bricks from the Sacred Architecture in Ancient Egypt to the Green House Revolution: (Case Study of Luxor City, Egypt) - Gelany A. F, Falana J. N., Reda Attalla (International Journal of Advanced Science and Technology, 2020)
Ancient Egyptians constructed houses, palaces, temples and tombs mainly of environmental stones and sometimes of mud bricks. Brick industry is one of the oldest industries in ancient Egypt, and it was known as “dbt” and “Dbt” in the ancient Egyptian language. Brick industry has been known in ancient Egypt since pre-dynastic times and antiquity. The bricks in the sacred architecture of the ancient Egyptian vary according to the purpose of the industry. The Torah confirmed the ancient Egyptian knowledge of making bricks from straw mixed with clay of the Nile. Pharos made mud brick from environmental materials such as clay and sand mixed with a binding material as straw. Mud bricks produced in Luxor, are made from clay and sand, Nile clay, Portland cement, white shale, red shale, and rarely in some villages used Minya lime brick in Luxor. Recently materials use for bricks production in Luxor are from four different types of source; (1) silt resulting from the disinfection of the Nile stream, (2) mud deposited from the Nile after the construction of the high dam, (3) quarried shale sediments nearest to the valley and now (4) quarried red shale. The production factories of bricks in Luxor producing two types of bricks; white brick and red brick depend on the quarried shale; sediments nearest to the valley or quarried red shale far from the valley. Therefore, this study investigates the structural order and properties of white bricks and red bricks using FT-IR spectroscopy and scanning electron microscope (SEM) method. The results obtain from this methods were discussed to evaluate the characteristic of both bricks. The conclusion of the study illustrates the reasons of the choice quarries, environmental materials and the evaluation of the industrial bricks in Luxor. Today, the mud-brick homes are one of the foundations of the green architecture revolution.